Online co-teaching: overcoming distance and spatial frontiers - Frigren Pirita; Ruiz Marie (COST European Cooperation in Science and Technology, 2025)
One member of COST Action Women on the Move (CA19112), Francesca Falk, once suggested to develop co-teaching classes between members of the network, and this has led to punctual interventions such as Vice-Chair Maija Ojala-Fulwood’s (Tampere University, Finland) in one online class for Veronika Capska’s course (Charles University, Czech Republic). WG2 co-leader Pirita Frigren and Chair Marie Ruiz decided to launch an experiment over a semester in a shared Master’s class entitled “Women on the Move – perspectives on historical and contemporary female migration”.